Trace minerals profile of blood and seminal plasma of breeding bulls* - DHAMI, A J; SHELKE, VINAYA B; PATEL, K P; PARADVA, J P; KAVANI, F S (The Indian Journal of Animal Sciences, 2014)
The trace minerals (Zn. Fe, Cu, Co, Mn) profile of blood plasma and seminal plasma was studied twice at monthly interval in 37 breeding bulls ofGir, Holstein Friesian, Jersey, crossbred and Jafarabadi buffalo breeds. The mean levels of these minerals (ppm) in the blood and seminal/plasma varied between different breeds. The differences between breeds were significant only for iron and copper in blood and for copper in seminal plasma. Zinc levels were 10-15 fold higher in seminal plasma than that in the blood plasma: iron and cappel levels were identical in both, while copper and manganese levels were 1.5 - 2.0 fold higher in blood compared to the seminal plasma in all the breeds. Jersey blood plasma had the lowest levels of zinc, iron and manganese. Whereas crossbreds and Jafarabadi bulls, respectively, had lowest copper and cobalt. Similarly, the lowest values for iron, copper and cobalt were seen in seminal plasma of Jafarabadi buffalo and those for zinc and manganese in crossbred and Jersey bulls respectively. The associations for zinc and copper between blood and semen were negative while those for iron, cobalt and manganese were positive. The significance ofthe findings has been discussed.